Crisis management during anaesthesia: regurgitation, vomiting, and aspiration. Issue 3 (2nd June 2005) - Kluger, M T; Visvanathan, T; Myburgh, J A; Westhorpe, R N
Abstract : Background: Regurgitation, vomiting and aspiration may occur unexpectedly in association with anaesthesia. "Aspiration/regurgitation" was ranked fifth in a large collection of previously reported incidents that arose during general anaesthesia. These problems are encountered by all practising anaesthetists and require instant recognition and a rapid, appropriate response. However, the diagnosis may not be immediately apparent as the initial presentation may vary from laryngospasm, desaturation, bronchospasm or hypoventilation to cardiac arrest. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK", supplemented by a specific sub-algorithm for regurgitation, vomiting and aspiration, in the management of these complications occurring in association with anaesthesia. Methods: The potential performance of this structured approach for each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS) was compared with the actual management as reported by the anaesthetists involved. Results: There were 183 relevant incidents of regurgitation, vomiting and aspiration among the first 4000 reports to the AIMS. Aspiration was documented in 96, was excluded in 69, and in 18 it could not be determined whether or not aspiration had occurred. It was considered that the correct use of an explicit algorithm would have led to earlier recognition and/or better management of the problem in 10% of all cases of regurgitation and vomiting and in 19% of those in which aspiration occurred. Conclusion: Regurgitation and/or aspiration should always be considered immediately in any spontaneously breathing patient who suffers desaturation, laryngospasm, airway obstruction, bronchospasm, bradycardia, or cardiac arrest. Any patient in whom aspiration is suspected must be closely monitored in an appropriate perioperative facility, the acuity of which will depend on local staffing and workload. If clinical instability is likely to persist or if there are concerns by attending staff, the patient should be admitted to a high dependency unit or intensive care unit.